Equilíbrio líquido-líquido para o sistema biodiesel de óleo de semente de melão (Cucumis melo l.) + metanol + glicerina - Sena, Suzara Rayanne de Castro (2014)
Rio Grande do Norte, northeast state from Brazil, it is the greatest producer and exporter of yellow melon, well known as Spanish melon. Despite the consumption of this fruit to be mainly its pulp, melon seeds are an important source of lipids considered an industrial residue it has been discharge product. The use of oilseeds in order to produce biodiesel establishes an important raw material and the increase of its production promotes the national development of the agriculture. In this background, the aim of this work has been to use oil from seeds of yellow melon to produce biodiesel and to accomplish a study of the phase equilibrium of the system evolving biodiesel, methanol and glycerin. The biodiesel was obtained by oil transesterification through methylic route with molar ratio 1:9.7 (oil:alcohol) and with a mass of NaOH of 0.5% from the oil mass; the reaction time was 73 minutes at 55 °C. A yield of 84.94% in biodiesel was achieved. The equilibria data present a well-characterized behavior with a great region of two phases. The tie lines indicate that methanol has a best solubility in the phase that is rich in glycerin. Consistency of the experimental data was made based on Othmer-Tobias and Hand correlations which values above 0.99 were found to correlation coefficients, this fact confers a good thermodynamic consistency to the experimental data. NRTL and UNIQUAC models were employed to predict liquid-liquid equilibrium of this system. It was observed a better concordance of the results when NRTL was applied (standard deviation 1.25%) although the UNIQUAC model has presented a quite satisfactory result either (standard deviation 2.70%). The NRTL and UNIQUAC models were also used to evaluate the effect of temperature in the range of 328 K to 358 K, in which a little change in solubility with respect to the data obtained at 298 K was observed, thus being considered negligible the effect of temperature